Особливості міжособистісної взаємодії у сім’ях працівників ОВС - Доценко, В. В.; Dotsenko, V. V.; Вікторія Доценко (Вісник Національного університету оборони України. - 2014. – Вип. 2 (39). – С. 199-203, 2014)
Стаття присвячена викладенню результатів емпіричного дослідження типів міжособистісної взаємодії у сім’ях працівників органів внутрішніх справ. Стилі спілкування розглядаються як основа благополуччя сім’ї. Визначено, що у родинах працівників ОВС трьох груп дослідження переважає авторитарний стиль міжособистісної взаємодії помірного та екстремального типів прояву. У жінокпрацівників ОВС, які незадоволені власним шлюбом, діагностовано переважання двох типів взаємодії: авторитарного та дружелюбного, що характеризує їх як дисгармонійну особистість.

The article is dedicated to the results of the empirical study of the interpersonal interaction types in the families of the law enforcement officers` families. The communication styles are considered as the basis for the family well-being. The research in three groups of law enforcement officers shows the prevalence of the autocratic style of the interpersonal interaction of the moderate and extreme types. The female part of the law enforcement employees, those who are not satisfied with their marriage, shows the prevalence of the autocratic and friendly styles. This characterises them as contradictory personality. The results received can be used for the improvement of the psychological system assurance of the law enforcement agencies activity and the family consultancy programmes development for the law enforcement officers` families for the interpersonal communication improvement in their families.

Статья посвящена изложению результатов эмпирического исследования типов межличностного взаимодействия в семьях работников органов внутренних дел. Стили общения рассматриваются как основа благополучия семьи. Определено, что в семьях работников ОВД трех групп исследования преобладает авторитарный стиль межличностного взаимодействия умеренного и экстремального типов. У женщин-сотрудников ОВД, которые неудовлетворенны своим браком, диагностировано преобладание двух типов взаимодействия: авторитарного и дружелюбного, что характеризует их как дисгармоничную личность.
Characteristics of interpersonalinteraction in the families members of police
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; сім’я; задоволеність – незадоволеність шлюбом; типи міжособистісної взаємодії; працівники ОВС; шлюб; міжособистісна взаємодія; удовлетворенность - неудовлетворенность браком; типы межличностного взаимодействия; работник милиции; працівник міліції; брак; межличностное взаимодействие; marriage satisfaction; marriage dissatisfaction; interpersonal interaction types; law enforcement officers